BUDAYA BERLADANG PETANI DI KESATUAN PENGELOLAAN HUTAN PRODUKSI (KPHP) BATULANTEH, KABUPATEN SUMBAWA (The culture of farming by farmers in the Production Forest Management Unit (KPHP) of Batulanteh, Sumbawa regency) - Dian Diniyati; Budiman Achmad (Jurnal Agroforestri Indonesia, 2020)
Farming is the main livelihood of farmers in Sumbawa which is culturally heritated in their live. The purpose of this study is to describe the culture of farming carried out by farmers so that the development policy making  can be more directed. This activity was carried out in the Sumbawa Batulanteh KPHP area in August and October 2016. Data were collected through open interviews with 34 respondents living in the area and 34 respondents living outside the area, while the collected data was analyzed descriptively. The total area of arable land by farmers living in the area was 1 hectare per head of household (hh),  while those living outside the area were 1.75 hectare / hh. The results of the study showed that farming activities were carried out on arable land and on private land. The longest distance of arable land to the location of residence was 3 km. Agroforestry patterns were chosen by farmers to meet economic and environmental goals. Farmers were not only trying to meet their daily consumption needs, but also their investment needs. Farming activities were influenced by the season, where during the rainy season the activities were planting, whereas during the dry season the activities were only in the form of land preparation. Farmer culture in clearing land was by chopping and burning because it was cheaper and easier, while at harvest time, the waste was returned to the field as compost to fertilize the soil.